Effect of fatty acid composition on ignition behavior of straight vegetable oils measured in a constant volume combustion chamber apparatus. (1st November 2017) - Plank, Matthias; Wachtmeister, Georg; Thuneke, Klaus; Remmele, Edgar; Emberger, Peter
Highlights: Ignition behavior of eleven different vegetable oils was analyzed. Ignition behavior was correlated to their fatty acid composition. Increasing unsaturation of the oils led to longer ignition delays. Increasing chain length had a minor effect on ignition delay. Abstract: Straight vegetable oils attracted attention several times as alternative fuel for mobile machinery. Certain efforts have already been undertaken to enable the usage of the high viscous oils in compression ignition engines. While physical properties are well specified for different kind of oils, only few information is available on the ignition behavior of vegetable oils under modern engine like conditions. Therefore, the ignition behavior of nine different vegetable oils and two oil mixtures was investigated using the Advanced Fuel Ignition Delay Analyser (AFIDA). The AFIDA is a modern constant volume combustion chamber apparatus equipped with a high pressure injection system. Analysis was performed at combustion chamber temperatures ranging from 796 K to 967 K and at air density levels of 4.7 kg/m 3, 9.3 kg/m 3 and 17.7 kg/m 3 . Ignition behavior was correlated to the structure indices average number of carbon atoms and average number of double bonds. Both were calculated using the fatty acid composition of the oils. Ignition delay decreased with rising temperature and air density. Coconut oil ignited first at every temperature except for the lowest air density level. Start of combustion was always last for linseed oil, followed by camelina and soybean oil. Ignition delay increased linearly with rising average number of double bonds and decreasing average number of carbon atoms. The effect of the average number of double bonds on ignition delay was more pronounced than that of carbon chain length. Fatty acids with two or more carbon-carbon double bonds led mostly to a stronger increase in ignition delay compared to those with only one double bond.